2010
DOI: 10.1007/s13197-010-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of low-fat pork sausages with tomato powder as colour and functional additive during refrigerated storage

Abstract: Low fat pork sausages were formulated with tomato powder at 0% (C), 0.8% (T1), 1.2% (T2) and 1.5% (T3) levels in basic formula. With the increase in tomato powder concentration the lightness of the sausage decreased but the redness and yellowness increased significantly (p< 0.05). The pH values of T2 and T3 were significantly (p< 0.05) lower than the others, whereas, water holding capacity of T2 and T3 was significantly (p<0.05) higher. Thiobarbituric acid reactive substances, cohesiveness and springiness valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 26 publications
5
43
2
Order By: Relevance
“…Xiong et al (1999) reported that polysaccharides and proteins in food interact through electrostatic association (attraction and repulsion) between the polar and non-polar groups of gums and proteins, resulting in pH variations. Choi et al (2009) obtained opposite results to those of the present study; they found higher pH (6.46 to 6.47) in sausages formulated with vegetable oil and rice bran fiber; these authors attributed this phenomenon to the minerals, such Kim et al (2011) stated that the decrease of pH in sausages is affected by the ingredients used in the formulation. In this research, the decrease in the sausage pH may be due to the pectin pH (4.3).…”
Section: Phcontrasting
confidence: 99%
“…Xiong et al (1999) reported that polysaccharides and proteins in food interact through electrostatic association (attraction and repulsion) between the polar and non-polar groups of gums and proteins, resulting in pH variations. Choi et al (2009) obtained opposite results to those of the present study; they found higher pH (6.46 to 6.47) in sausages formulated with vegetable oil and rice bran fiber; these authors attributed this phenomenon to the minerals, such Kim et al (2011) stated that the decrease of pH in sausages is affected by the ingredients used in the formulation. In this research, the decrease in the sausage pH may be due to the pectin pH (4.3).…”
Section: Phcontrasting
confidence: 99%
“…AP addition decreased pH values (P<0.05) of frankfurter samples, this decrement in pH could be attributed to the acid nature of AP (pH 4.9). Similar results were reported previously (Eyiler and Öztan, 2011;Kim et al, 2011) in sausages formulated with different amounts of tomato powder and raw pork burgers formulated with passion fruit albedo (López-Vargas et al, 2014). However, Savadkoohi et al (2014), reported no changes in pH values of sausages formulated with tomato pomace.…”
Section: Proximate Analysis Ph and Energy Valuesupporting
confidence: 86%
“…It has been showed that 5% or 10% plum puree improved cooking characteristics of beef patties without any detrimental effects on sensory properties (Yıldız-Turp and Serdaroglu, 2010). Low fat pork sausage with tomato powder up to 1.5% was found to be well acceptable up to 30 days at refrigerated storage (Kim et al, 2011). Guava powder increased dietary fiber, reduced emulsion stability in chicken nuggets (Verma and Sahoo, 2000).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More and more literatures implicate that supplementation of food rich in lycopene is associated with the decrease of risk of cardiovascular diseases and cancers (Rao and Agarwal 1999;Kim et al 2011). So lycopene has important and significant commercial value (Mysore Doddaiah et al 2011;Gunjan et al 2009).…”
Section: Introductionmentioning
confidence: 99%